(untitled) - Yolen, Jane; Stemple, Heidi E. Y.; Nobati, Eugenia (Minneapolis, 2022)
"This appealingly icky poetry collection presents animals that suck-quite literally! From the mosquito to the elephant to the lamprey, discover how and why these animals sip, slurp, and suck"--
Includes bibliographical references.
Keywords: Animals; Food; Animals; Miscellanea; Food; Juvenile literature; Animals; Miscellanea; Animals